2013
DOI: 10.1002/j.1532-2149.2013.00415.x
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of peripheral neuropathic pain by topical capsaicin: Impact of pre‐existing pain in the QUEPP‐study

Abstract: BackgroundThis study evaluates the impact of the duration of pre-existing peripheral neuropathic pain on the therapeutic response to the capsaicin 8% cutaneous patch.MethodsThe non-interventional QUEPP (QUTENZA – safety and effectiveness in peripheral neuropathic pain) study evaluated the effectiveness of Qutenza™ in 1044 non-diabetic patients with peripheral neuropathic pain, who received a single application. Follow-up visits were scheduled at weeks 1–2, 4, 8 and 12. A pre-defined co-analysis of changes in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
43
0
7

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(52 citation statements)
references
References 25 publications
2
43
0
7
Order By: Relevance
“…In other pNP syndromes, ≥30% pain relief was achieved in only about 50% of patients . Only short disease durations, <6 months, predicted treatment response independently from the underlying diagnoses (Maihofner and Heskamp, 2013b). Only short disease durations, <6 months, predicted treatment response independently from the underlying diagnoses (Maihofner and Heskamp, 2013b).…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…In other pNP syndromes, ≥30% pain relief was achieved in only about 50% of patients . Only short disease durations, <6 months, predicted treatment response independently from the underlying diagnoses (Maihofner and Heskamp, 2013b). Only short disease durations, <6 months, predicted treatment response independently from the underlying diagnoses (Maihofner and Heskamp, 2013b).…”
Section: Introductionmentioning
confidence: 92%
“…Self-reported sensory symptoms failed to identify responders (Hoper et al, 2013). Only short disease durations, <6 months, predicted treatment response independently from the underlying diagnoses (Maihofner and Heskamp, 2013b). So far, other predictors for positive outcome remain unknown.…”
Section: Introductionmentioning
confidence: 96%
“…Three studies have found correlation with pain and response to treatment [26][27][28]. Although, the correlation is not the same, and the quality of pain investigated was different too.…”
Section: Pain As a Predictor Of Response To Treatmentmentioning
confidence: 99%
“…At present, there are no reliable predictors of response to treatment with capsaicin for analgesia. There have been several studies that have tried to look for predictors of treatment response [26][27][28][29][30][31]. In this chapter we are going to comment on them trying to give more light into this issue.…”
Section: Introductionmentioning
confidence: 99%
“…Les résultats de cette étude confirment l'efficacité de Qutenza ® observée dans les essais cliniques, avec une réduction du score de douleur de -27 % dès la 2 e semaine et maintenue jusqu'à 3 mois et ce, quelle que soit l'étiologie. Une analyse [31] en sousgroupe selon l'ancienneté de la douleur a été effectuée et montre une meilleure efficacité du patch lors d'une prise en charge précoce (douleur évoluant depuis moins de 6 mois).…”
Section: Patch De Capsaïcine à Haute Concentrationunclassified